Development of solar photovoltaic model for wide range of operating conditions - Mohammed Asim; Adil Sarwar; Mohammad Shahabuddin; Mohammad Saood Manzar (Institute of Advanced Engineering and Science, 2021)
Assorted climatic conditions such as irradiation, temperature and shading due to clouds, trees, buildings, communication towers etc. has an unavoidable impact on the output of solar photovoltaic (PV) system. This creates a need for the analytical performance study of solar PV system in changing atmospheric condition in order to design and install an optimized solar PV system for both, stand alone and grid connected. The present work shows the developed PV model in MATLAB codes and simulation is done under varying climate conditions showing change in irradiation and temperature using different arrangements of PV system. PV parameters are obtained in different setup and I-V and P-V characteristics of the developed model of the PV modules are analyzed. A comparative study of the parameters obtained is quite beneficial for an optimized design of the PV system under different atmospheric conditions.